2021
DOI: 10.1002/ptr.7043
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and pleiotropic effects of Phyllanthus emblica extract as an add‐on therapy in patients with essential hypertension—A randomized double‐blind placebo‐controlled trial

Abstract: Essential hypertension is an important cause of cardiovascular morbidity and mortality that is compounded by concomitant risk factors like diabetes mellitus and dyslipidemia. Phyllanthus emblica is a rich source of antioxidants, tannins, and vitamin C and is used in treating various ailments in traditional medicine. This study aimed to elucidate the effects of aqueous extract of Phyllanthus emblica on essential hypertension and other protective actions. This randomized controlled trial was conducted on 150 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Based on a randomized control trial done in Japan among hypertensive adults complementing herbs, it was found that only total cholesterol and triglyceride categories differed from the hypertensive participants in this present study (42). Similarly, a trial done in India with consumption of gooseberries among hypertensive adults differed in HDL and triglyceride aspects (43). Thus, it can be said that the lipid parameters tend to vary among participants across studies carried out in different countries, but mostly had borderline high triglyceride levels which was the same as the overall mean for this present study.…”
Section: Highsupporting
confidence: 52%
“…Based on a randomized control trial done in Japan among hypertensive adults complementing herbs, it was found that only total cholesterol and triglyceride categories differed from the hypertensive participants in this present study (42). Similarly, a trial done in India with consumption of gooseberries among hypertensive adults differed in HDL and triglyceride aspects (43). Thus, it can be said that the lipid parameters tend to vary among participants across studies carried out in different countries, but mostly had borderline high triglyceride levels which was the same as the overall mean for this present study.…”
Section: Highsupporting
confidence: 52%
“…The synthesis rate and amount of hs-CRP, a marker of the inflammatory response, are both low in a healthy individual. When the body suffers from inflammation and injury, the expression of hs-CRP can increase rapidly within a short time, playing an important role in regulating the function of phagocytes, activating complement, and eliminating apoptosis, necrosis, and damaged cell tissues in the body[ 19 , 20 ]. The results of this study showed that the expression of hs-CRP in the control group was < Grade 1 hypertension group < Grade 2 hypertension group < Grade 3 hypertension group, indicating that high expression of hs-CRP might be an important factor leading to the progression of PH and induction of a prethrombotic state.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have reported that YGZ and its extracts could protect RAW264.7 cells from H 2 O 2 -induced toxicity, reduce the size of atherosclerotic plaques, and inhibit endothelin-1 (ET-1) expression. [33][34][35] Moreover, it could exert antiinflammatory effects by reducing the expression of nitric oxide (NO) and proinflammatory cytokines. 36 In addition, it could protect β-cells, scavenge-free radicals, alleviate inflammation, and reduce advanced glycation end products.…”
Section: Discussionmentioning
confidence: 99%